Subtotal laryngectomy with formation of a laryngotracheal shunt in vocal rehabilitation of patients with stage III and IV locally advanced larynx and laryngopharynx cancer (literature review) - E. N. Menkova; D. E. Kulbakin; E. A. Krasavina; M. R. Mukhamedov; V. A. Alekseev; V. I. Shtin (Опухоли головы и шеи, 2021)
Currently accepted standard of surgical treatment of patients with locally advanced stage III and IV laryngeal and laryngopharyngeal cancer is laryngectomy which leads to loss of vocal function. Therefore, vocal rehabilitation is one of the most important tasks of the doctor. It allows to increase quality of life of patients after treatment. Currently used techniques of vocal rehabilitation have their advantages and disadvantages. The article considers various techniques of vocal rehabilitation, primarily, subtotal laryngectomy with laryngotracheal shunt as a promising method of surgical rehabilitation of patients with locally advanced caner of the larynx and laryngopharynx.